Considerations on Speaking Communication (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the views of scientists about communication and speech communication, the tools that create speech communication, the model of speech communication, the stages of communication, internal and external factors affecting communication, verbal and nonverbal means, and scientific and theoretical views from the works of Erkin A’zam reinforced by examples.